Initial TLC, NLR, LDH, CRP, D-Dimer, and Procalcitonin in Intubated vs Non Intubated COVID-19 Patients - Ridha Surya Nugraha; Indriasari Indriasari; Ricky Aditya (Faculty of Medicine, Universitas Padjadjaran, 2022)
COVID-19 is an acute respiratory disease caused by the SARS-CoV-2 virus that has caused a pandemic with symptoms of upper respiratory infection, respiratory failure, and even mortality. Several asymptomatic patients, with no shortness of breath, were found to experience impaired oxygenation in examination for objective data (happy hypoxia). Thus, objective data are needed, including data on inflammatory parameters (TLC, NLR, LDH, CRP, D-dimer and PCT) to monitor the severity and prognosis of COVID-19 patients. This study aimed to evaluate the inflammatory parameters in the initial days of treatment for COVID-19 patients between intubated and non-intubated patients during hospitalization. The study was conducted in the COVID isolation ward of Dr. Hasan Sadikin General Hospital Bandung, Indonesia, from July 2020 to July 2021. This was a retrospective cross-sectional comparative analytical observational study that involved patients’ first laboratory examination results. The statistical analysis was performed using Mann Whitney test for numerical data and Chi Square test for categorical data. There were significant differences in inflammatory parameters values in both groups (p<0.01). The TLC values of intubated patients were lower than those of non-intubated patients, while the NLR, LDH, CRP, D-dimer and PCT values of intubated COVID-19 patients were higher than those of non-intubated patients.